2007
DOI: 10.1093/hmg/ddm007
|View full text |Cite
|
Sign up to set email alerts
|

FXYD1 is an MeCP2 target gene overexpressed in the brains of Rett syndrome patients and Mecp2-null mice

Abstract: Rett syndrome (RTT) is an X-linked neurodevelopmental disorder linked to heterozygous de novo mutations in the MECP2 gene. MECP2 encodes methyl-CpG-binding protein 2 (MeCP2), which represses gene transcription by binding to 5-methylcytosine residues in symmetrically positioned CpG dinucleotides. Direct MeCP2 targets underlying RTT pathogenesis remain largely unknown. Here, we report that FXYD1, which encodes a transmembrane modulator of Na(+), K(+) -ATPase activity, is elevated in frontal cortex (FC) neurons o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
142
3
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(161 citation statements)
references
References 57 publications
14
142
3
2
Order By: Relevance
“…MeCP2 regulation of neuronal differentiation is mediated through chromatin remodeling and its action on multiple target genes, most of which are still unknown. BDNF and FXYD1 are two genes repressed by MeCP2 repression (14,32,59). Consistent with the reduced MeCP2 levels detected in BDV-infected neurons, we demonstrated that mRNA levels for both BDNF and FXYD1 were significantly increased upon infection (Fig.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…MeCP2 regulation of neuronal differentiation is mediated through chromatin remodeling and its action on multiple target genes, most of which are still unknown. BDNF and FXYD1 are two genes repressed by MeCP2 repression (14,32,59). Consistent with the reduced MeCP2 levels detected in BDV-infected neurons, we demonstrated that mRNA levels for both BDNF and FXYD1 were significantly increased upon infection (Fig.…”
supporting
confidence: 86%
“…Transcript levels of brain-derived neurotrophic factor (BDNF), phospholemman (FXYD1), and the housekeeping gene HPRT were quantified using real-time quantitative PCR (ABI Prism 7000; Perkin-Elmer Applied Biosystems) and Sybr green DNA dye from a Sybr green I reaction system (Eurogentec, Angers, France). Primer sequences were as follows: forward primer 5Ј-CCCAGTCTCTGCCTAGATCAAATGG-3Ј and reverse primer 5Ј-ACTCGCACGCCTTCAGTGAGAA-3Ј for BDNF (32), forward primer 5Ј-AG TGCAGAAGCTCCGCAGGAA-3Ј and reverse primer 5Ј-TACCGCCTGCGG GTGGACAGA-3Ј (14) for FXYD1, and forward primer 5Ј-TGTTGGATACA GGCCAGACTTTGT-3Ј and reverse primer 5Ј-TCCACTTTCGCTGATGACA CA-3Ј (53) for HPRT.…”
mentioning
confidence: 99%
“…Three isoforms of the catalytic ␣ subunit, ␣1-3 (McGrail et al, 1991), and among seven isoforms (FXYD1-7) of the ␥ subunit that modulate NKA activity, FXYD1, 6, and 7, are highly expressed in the brain (Geering, 2006), whereas other members of FXYD proteins are expressed in other tissues in a tissue-specific way. Some of the brain-expressed NKA subunits are implicated in neuronal disorders (De Fusco et al, 2003;de Carvalho Aguiar et al, 2004;Deng et al, 2007), which are attributable to the role of NKA [e.g., its role in the propagation of action potentials, defensive roles against excitotoxicity that induces elevation of intracellular concentrations of Na ϩ and Ca 2ϩ ions (Brines and Robbins, 1992;Mark et al, 1995;Kiedrowski et al, 2004), and its roles in postsynaptic functions (Reich et al, 2004;Zhang et al, 2009)]. …”
Section: Introductionmentioning
confidence: 99%
“…Subsequent procedures were performed as described elsewhere. 54 Chromatin was sheared with a Bioruptor (Diagenode) to an average length of 300-600 bp. The following antibodies were used: rabbit polyclonal anti-Mecp2 (Abcam), anti-total histone H3 (Abcam), negative control IgG antiserum (Upstate Biotechnologies).…”
mentioning
confidence: 99%